The comprehensive textbook of healthcare simulation - DeMaria Jr., Samuel; Schwartz, Andrew D.; Sim, Alan J.; Levine, Adam I. (Springer New York, 2013)
The Comprehensive Textbook of Healthcare Simulation is a cohesive, single-source reference on all aspects of simulation in medical education and evaluation.  It covers the use of simulation in training in each specialty and is aimed at healthcare educators and administrators who are developing their own simulation centers or programs and professional organizations looking to incorporate the technology into their credentialing process.  For those already involved in simulation, the book will serve as a state-of-the-art reference that helps them increase their knowledge base, expand their simulation program's capabilities, and attract new, additional target learners. Features: •  Written and edited by pioneers and experts in healthcare simulation •  Personal memoirs from simulation pioneers •  Each medical specialty covered •  Guidance on teaching in the simulated environment •  Up-to-date information on current techniques and technologies •  Tips from "insiders" on funding, development, accreditation, and marketing of simulation centers •  Floor plans of simulation centers from across the United States •  Comprehensive glossary of terminology